Pengaruh Partisipasi Anggaran, Budget Emphasis, Kompleksitas Tugas, Dan Komitmen Organisasi Terhadap Slack Anggaran(Studi Kasus Pada Satuan Kerja Perangkat Daerah Kota Surakarta) - Afriyanti, Titi; , Dr. Triyono, SE., M.Si (2016)
The aim of study examines the effect of budgetary participation, budget emphasis, task complexity, and organizational commitment on budgetary slack. The research design used was a quantitative one. The population consisted of 21 unit of local goverment office involved in the budgeting process at Surakarta local goverment. The sample were determined based on purposive sampling technique. The data were collected based on a survey method by distributing questionnaires directly to the respondents. The Analysis method used multiple linear regression. The result of this research partisipation budgeting, budget emphasis, and task complexity has significant influence on budgetary slack, whil as organizational commitment is not significant influence on budgetary slack.